2016
DOI: 10.1016/j.bpj.2016.08.027
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Mapping of a Repeat Protein Folding Free Energy Landscape

Abstract: A complete description of the pathways and mechanisms of protein folding requires a detailed structural and energetic characterization of the conformational ensemble along the entire folding reaction coordinate. Simulations can provide this level of insight for small proteins. In contrast, with the exception of hydrogen exchange, which does not monitor folding directly, experimental studies of protein folding have not yielded such structural and energetic detail. NMR can provide residue specific atomic level s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 33 publications
1
49
0
Order By: Relevance
“…Furthermore, alternative states may be elicited by pressure perturbation and studied by NMR spectroscopy (14,15). Relative populations of excited states are shifted under pressure as a result of associated volume differences, which includes the loss of cavities or packing defects in the protein interior (16), cavity hydration (17)(18)(19), local and global unfolding (20)(21)(22), and structure relaxation from side-chain rearrangement (23). As internal cavities make a major contribution to the total volume change upon protein structural transition, hydrostatic pressure emerges as a key variable to the study of protein excited states (16).…”
mentioning
confidence: 99%
“…Furthermore, alternative states may be elicited by pressure perturbation and studied by NMR spectroscopy (14,15). Relative populations of excited states are shifted under pressure as a result of associated volume differences, which includes the loss of cavities or packing defects in the protein interior (16), cavity hydration (17)(18)(19), local and global unfolding (20)(21)(22), and structure relaxation from side-chain rearrangement (23). As internal cavities make a major contribution to the total volume change upon protein structural transition, hydrostatic pressure emerges as a key variable to the study of protein excited states (16).…”
mentioning
confidence: 99%
“…To visualize more precisely which regions of the protein become disordered at intermediate pressures, we constructed fractional contact maps (22) for I27 single-module. We define the probability of contact for any pair of residues, P i,j , as the geometric mean of the fractional probability that each of the two residues is in the folded state at a given pressure (P ij = [P i x P j ] 1/2 ) (26). The pressure dependence of the contact maps showed that the region first affected by an increase of pressure is the short parallel ß-sheet (Strands A’G).…”
Section: Resultsmentioning
confidence: 99%
“…Native contact maps were obtained by using software CMView (36) with a threshold of 9 Å around the Cα of each residue, using the best structure among the 20 refined ones. Using the geometric mean, rather than the joint probability as previously done (22,26), ensures the correct unfolding profile in the case of two-state unfolding.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…see Ref. 136). In addition, conformational distributions from folding simulations may be used to predict time-resolved experimental results.…”
Section: Harnessing the Predictive Power Of Folding Simulationsmentioning
confidence: 95%